Associations Between Internet and Traditional Media Usage and Users’ Attitudes Toward Wife-Beating in Nigeria - Ola, Bamidele Emmanuel (Journal of Population and Social Studies [JPSS], 2023)
This study quantitatively examines the associations between the Internet and traditional media (e.g., television, radio, newspapers) usage and users’ attitudes toward wife-beating in Nigeria. Data from the 2018 Nigeria Demographic and Health Survey involving 13,311 men (aged 15 to 59 years) and 41,821 women (aged 15 to 49 years) were analyzed using multiple logistic regression models. The central question was whether frequent Internet and traditional media users significantly differed in their attitudes toward wife-beating justification compared to individuals who seldom used these media channels in Nigeria. The results showed that Nigerian online media users were substantially less likely to approve of wife-beating compared to their non-users. However, for traditional media usage, only radio usage was significantly associated with a reduced likelihood of wife-beating approval among women. Newspaper usage was associated with a higher level of justification, while television was not significantly related to wife-beating support. This study emphasizes the need for the Nigerian media channels to effectively join the international campaigns seeking to eliminate intimate partner violence against women (IPVAW).